Tinjauan Terpadu terhadap Terapi Presisi dan Standardized Herbal Drug untuk Non-Alcoholic Fatty Liver Disease (NAFLD): Kemajuan Molekuler, BuktiKlinis, serta Implikasi Integratif - Raymond R. Tjandrawinata (PT Dexa Medica, 2025)
Non-alcoholic fatty liver disease (NAFLD) is a progressive hepatic disorder that has become a central component of the global metabolic syndrome spectrum. Its complex pathogenesis involves insulin resistance, chronic inflammation,oxidative stress, and activation of fibrogenic pathways. Along with the deepening understanding of molecular mechanisms,precision therapies targeting farnesoid X receptor (FXR) agonists, peroxisome proliferator-activated receptor (PPAR) modulators, incretin mimetics, and RNA-based technologies are being developed, although challenges remain concerningside effects and accessibility. In this context, Veprolin containing Proliverenol, a bioactive fraction of Phaleria macrocarpa, offers potential as an adjuvant standardized herbal drug with anti-inflammatory, antifibrotic, and reparative effects, as demonstrated in preclinical studies. This review highlights the importance of integrative, precision-oriented, and sustainable multimodal therapeutic strategies.